Kriterii, ocenka i korrekcija techniceskogo masterstva sportsmenov v sovremennych predstavlenijach i technologijach - Rostovtsev, V. L.; Grushin, A. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article provides the substantiation and basic provisions of the methodology for assessing and correcting the technique of movement in cyclic sports (for example, running, skiing and cycling) using technical means and digital technologies - software (software) with elements of artificial intelligence. An objective assessment of the level of technique of movements in cyclic sports is possible when organizing an urgent transfer to an athlete of informative indicators of mechanical efficiency and economy of movement in a special structure of locomotions. The methodology is based on the determination of the main functional (limiting) link (GFZ), synchronous visual informing the athlete about the indicators of the levels of this link, the efficiency of the special structure of movement and the timely delivery of a stimulating impulse. In running, the GFZ is the moment of landing. In cross-country skiing, the take-off moment. In cycling, the pressure on the pedals is uniform throughout the cycle. In each of the sports, in order to correct the technique of movement, elements of the effective influenceof auxiliary means are necessary, which make it possible to increase the resolution of controlling the parameters of one`s movement and / or additional stimulation at the moment of the GFG.